MEDICAL COLLEGE STUDENTS HEALTH CHANGES DURING THE STUDY PERIOD - Geske, Rita; Leice, Alevtīna; Strode, Iveta; Lāce, Maira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The goal of this research is to analyze the change of students’ physical health during the one year of studies in context of lifestyle. The research participants were 103 Medical College’s students aged 19 to 56 years. All tests, measurements and questionnaires were done at falls of 2015 and 2016. Students’ physical health was evaluated in accordance with Apanasenko’s methods based on investigative anthropometric and functional testing measurements. These measurements included body mass index, lungs vital capacity, strength index, Robinson index and Recovery Heart Rate. Students’ lifestyle habits were determined with the help of questionnaire that included question groups regarding the self-evaluation of health status, health problems and illnesses, eating habits, and physical activities. During the research, lipid parameters in blood were also measured determining the total cholesterol (TC), high-density lipoprotein (HDL) and low-density lipoprotein (LDL).